A review on different level of water towards rice growth / Amirul Fatyhah Adnan - Adnan, Amirul Fatyhah (Faculty of Plantation and Agrotechnology, 2017)
Rice is the second most important crop in the world after wheat, with Asia being the largest producer and consumer. The National Agrofood Policy of Malaysia, 2011-2012 (Dasar Agromakanan Negara, DAN) had highlighted that local rice production should be increased to ensure the country's demand in future. However, to produce the high production of the rice we need to start with water management which mean supply enough and suitable water level for the rice growth. The objective of this study is to estimate the suitable or the best water level that need by the rice growth because every stage of rice growth need different water level and need different irrigation management. Every stage needs different level of water because in every stage rice plants involve different growth process because in vegetative stage in involve the transplants to panicle initiation, second stage that is stage reproductive activities include from panicle initiation to flowering and the duration approximately is about one month that need a lots of water supply for the rapid growth and last stage is ripening stage that the phase starts from flower bloom to maturity and generally this blooming phase takes about 25-35 days before it start to pollinate. As the result, the production of the rice yield will increase and the weed population can be control because the rice field had being supply enough water from vegetative until ripening stage of the rice growth.